2016
DOI: 10.4172/pharmaceutical-sciences.1000120
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Ganciclovir Loaded Glutathione Modified Gold Nanoparticles

Abstract: Kiroula, et al.: Glutathione-modified Gold Nanoparticles of GanciclovirThis article reports that ganciclovir-loaded gold nanoparticles were developed via glutathione surface modification. Citrate-reduced gold nanoparticles were prepared first from chloroauric acid. Further the surface of gold nanoparticles was modified with glutathione. Then ganciclovir was loaded onto the glutathione-modified gold nanoparticles through the reaction between carboxyl group of glutathione and amino group of ganciclovir. Gold nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…All the peaks characterizing flavonoids were observed. These results were in good agreement with those of Kiroula et al (2016) and Sulaiman et al (2020) [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 93%
“…All the peaks characterizing flavonoids were observed. These results were in good agreement with those of Kiroula et al (2016) and Sulaiman et al (2020) [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 93%
“…GSSG Synthesis of AuNPs via citrate reduction of AuCl3 was proven successful as UV-vis spectroscopy revealed maximum absorbance (Absmax) in the UV-vis spectrum (Figure 1) occurred at wavelength 518 nm. Absmax achieved aligned with previous findings that showed SPR properties of AuNPs can be observed in the range of 500 -600 nm [1], [3], [5], [21]- [23].…”
Section: A Characterization Of Synthesized Aunps and Aunp-supporting
confidence: 89%
“…Moreover, the peak at 1391 cm -1 indicated the intensity of C-OH deformation vibration, which likely arose from surface-bound sodium citrate. In short, the results showed that the sodium citrate moieties are attached to the surface of rGO and act as a capping agent which stabilizes the rGO [23].…”
Section: Resultsmentioning
confidence: 97%